2016
DOI: 10.1002/anie.201509216
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Chemical Reporters for Selective In Situ Probing of Mycomembrane Components in Mycobacteria

Abstract: The global pathogen Mycobacterium tuberculosis and other species in the suborder Corynebacterineae possess a distinctive outer membrane called the mycomembrane (MM). The MM is composed of mycolic acids, which are either covalently linked to an underlying arabinogalactan layer or incorporated into trehalose glycolipids that associate with the MM non-covalently. These structures are generated through a process called mycolylation, which is central to mycobacterial physiology and pathogenesis and is an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(122 citation statements)
references
References 38 publications
9
113
0
Order By: Relevance
“…30 Our group recently developed a class of alkyne-modified TMM (AlkTMM) analogues ( 7 and 8 ), which could deliver alkyne-modified mycolic acid mimics to either TDM or AGM via the action of Ag85, thus tagging the lipid portions of these molecules. 31 Together, these studies revealed two routes by which trehalose-based probes can incorporate detectable tags into mycobacteria: (i) anchoring to the cell wall via periplasmic Ag85-mediated mycoloylation; (ii) accumulation in the cytoplasm via uptake through SugABC-LpqY, with possible downstream incorporation into trehalose glycolipids. FITC-Tre, TreAz, and AlkTMM analogues enabled cellular imaging and provided valuable information about targeting trehalose metabolic pathways, but their reliance on optical imaging for detection and, in the case of TreAz and AlkTMM analogues, a secondary labeling step, are not ideally suited to in vivo imaging applications.…”
Section: Introductionmentioning
confidence: 94%
“…30 Our group recently developed a class of alkyne-modified TMM (AlkTMM) analogues ( 7 and 8 ), which could deliver alkyne-modified mycolic acid mimics to either TDM or AGM via the action of Ag85, thus tagging the lipid portions of these molecules. 31 Together, these studies revealed two routes by which trehalose-based probes can incorporate detectable tags into mycobacteria: (i) anchoring to the cell wall via periplasmic Ag85-mediated mycoloylation; (ii) accumulation in the cytoplasm via uptake through SugABC-LpqY, with possible downstream incorporation into trehalose glycolipids. FITC-Tre, TreAz, and AlkTMM analogues enabled cellular imaging and provided valuable information about targeting trehalose metabolic pathways, but their reliance on optical imaging for detection and, in the case of TreAz and AlkTMM analogues, a secondary labeling step, are not ideally suited to in vivo imaging applications.…”
Section: Introductionmentioning
confidence: 94%
“…104 As hypothesized, metabolic labeling experiments confirmed that O-AlkTMM predominantly incorporated into the AGM layer via the action of Ag85. O-AlkTMM also exhibited high specificity for mycobacteria, as it robustly labeled M. smegmatis and the related species C. glutamicum , but it did not label Gram-negative E. coli or Gram-positive Bacillus subtilis .…”
Section: Applications Of Trehalose Analoguesmentioning
confidence: 54%
“…104 Such experimental flexibility will facilitate the study of cell envelope dynamics in intact mycobacterial cells. Recently, we also observed that O-AlkTMM can label and facilitate the identification of proteins modified by mycoloyl groups in C. glutamicum .…”
Section: Applications Of Trehalose Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main constituents of the Mtb cell envelope include: a plasma membrane, a cell wall core consisting of peptidoglycan in covalent attachment with arabinogalactan and mycolic acids, outer membrane lipids referred to as the mycomembrane and a loosely attached capsule. 2-4 The outer membrane gives Mtb a cell wall architecture similar to Gram negative bacteria. The arabinogalactan and trehalose are found in the cell wall as esters of mycolic acids (MAs).…”
Section: Introductionmentioning
confidence: 99%